A Study On Overall Equipment Effectiveness (OEE) For Performance Measurement Case Study For Surface Mount Technology (SMT) Department - Shamsudin, Siti Nor Atiqah (Universiti Sains Malaysia, 2018)
Efficiency and effectiveness are buzzwords in today’s fluctuating and competitive market. The greater the efficiency and effectiveness, the more productive is the organization. Many organizations are forced to implement various productivity improvement programs in order to continue to cope with the complexities and survive in today's turbulent and competitive business environment. Performance measurement is the language of progress, and provides a sense of where we are and more importantly where we are going. There are many reasons for companies to measure performance. By measuring the performance, the company can improved control, since feedback is essential for any system. Furthermore, clear responsibilities and objectives can be seen, because good performance measures clarify who is responsible for specific results or problems and also helps in understanding business processes. This is because measuring data requires an understanding of the manufacturing process. Overall Equipment Effectiveness (OEE) is such a performance measure, which indicates current status of production. OEE is one of the metric used for identifying losses, benchmarking progress, and improving the productivity of manufacturing equipment.However, having the OEE matrices without proper understanding of the occurrence of losses will hinder improvement of the process. This research was conducted to study and analyse on how the OEE matrices are used to measure the performance at the Surface Mount Technology (SMT) Department. The six big losses mainly are identified and Pareto analysis method was used and it is found that non-scheduled time and changeover activity contribute to the greatest loss. Thus, single minute exchange dies (SMED) technique was recommended to reduce time taken for the changeover. This project indicate that OEE is a powerful yardstick that can be used by companies to measure their performance.